Autoantibody testing by enzyme-linked immunosorbent assay-a case in which the solid phase decides on success and failure. Issue 1 (January 2020) - Deutschmann, Claudia; Roggenbuck, Dirk; Schierack, Peter; Rödiger, Stefan
Abstract: Background: The enzyme-linked immunosorbent assay (ELISA) is an indispensable tool for clinical diagnostics to identify or differentiate diseases such as autoimmune illnesses, but also to monitor their progression or control the efficacy of drugs. One use case of ELISA is to differentiate between different states (e.g. healthy vs. diseased). Another goal is to quantitatively assess the biomarker in question, like autoantibodies. Thus, the ELISA technology is used for the discovery and verification of new autoantibodies, too. Of key interest, however, is the development of immunoassays for the sensitive and specific detection of such biomarkers at early disease stages. Therefore, users have to deal with many parameters, such as buffer systems or antigen-autoantibody interactions, to successfully establish an ELISA. Often, fine-tuning like testing of several blocking substances is performed to yield high signal-to-noise ratios. Methods: We developed an ELISA to detect IgA and IgG autoantibodies against chitinase-3-like protein 1 (CHI3L1), a newly identified autoantigen in inflammatory bowel disease (IBD), in the serum of control and disease groups (n = 23, respectively). Microwell plates with different surface modifications (PolySorp and MaxiSorp coating) were tested to detect reproducibility problems. Results: We found a significant impact of the surface properties of the microwell plates. IgA antibody reactivity was significantly lower, since it was in the range of background noise, when measured on MaxiSorp coated plates (p < 0.0001). The IgG antibody reactivity did not differ on the diverse plates, but the plate surface had a significant influence on the test result (p = 0.0005). Conclusion: With this report, we want to draw readers' attention to the properties of solid phases and their effects on the detection of autoantibodies by ELISA. We want to sensitize the reader to the fact that the choice of the wrong plate can lead to a false negative test result, which in turn has serious consequences for the discovery of autoantibodies. Abstract : Biochemistry; Coatings; Surface chemistry; Immunology; Proteins; Laboratory medicine; Clinical research; Enzyme-linked immunosorbent assay; Biomarker discovery; Reproducibility; Solid-phase; Autoantibody